PENERAPAN COOPERATIVE LEARNING TIPE SNOWBALL THROWING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN AKIDAH AKHLAK - Dadang (Pascasarjana Unviersitas Majalengka, 2020)
This research was conducted at MTS 7 Negeri Majalengka which was motivated by a decline in the value obtained by students in the field of the Akidah Akhlak subjects. This study aims to apply the Snowball Type Cooperative Learning model in order to increase the enthusiasm and motivation of students in attending the Akidah Akhlak lessons. The research method used in this study uses quantitative descriptive research methods that use classroom action research based on the research cycle. The results showed that empirically there was an increase in the learning process from the first cycle to the second cycle. These results indicate that the Snowball Cooperative Learning model is considered quite successful in improving student learning outcomes.